Obesity and socioeconomic status in developing countries: a systematic review - Dinsa, G. D; Goryakin, Y; Fumagalli, E; Suhrcke, M (Obesity reviews, 2012)
We undertook a systematic review of studies assessing the association between socioeconomic status (SES) and measured obesity in low‐ and middle‐income countries (defined by the World Bank as countries with per capita income up to US$12,275) among children, men and women. The evidence on the subject has grown significantly since an earlier influential review was published in 2004. We find that in low‐income countries or in countries with low human development index (HDI), the association between SES and obesity appears to be positive for both men and women: the more affluent and/or those with higher educational attainment tend to be more likely to be obese. However, in middle‐income countries or in countries with medium HDI, the association becomes largely mixed for men and mainly negative for women. This particular shift appears to occur at an even lower level of per capita income than suggested by an influential earlier review. By contrast, obesity in children appears to be predominantly a problem of the rich in low‐ and middle‐income countries.